Upacara Seren Taun Masyarakat Sunda Sebagai Media Pendidikan Karakter di Sekolah Dasar - Resa Respati; Tati Narawati; Trianti Nugraheni (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
Education is an educational process to educate children. Education does not only make children smart and skilled, but education also has a more important goal, namely to make children have a good attitude. This change in attitude occurs because of the veil of values through character education. Currently, character values in children have begun to fade due to the influence of various technological advances in all fields. This will certainly facilitate and speed up the entry of foreign values and culture that are not yet known about the good and bad for children. Efforts to cover national character can be done by combining aspects of education and aspects of local culture. In practice, local coloring is colored with a variety of positive values that can be used as meaning in living life. This study aims to analyze the character values contained in the Sundanese seren taun ceremony. The method used is descriptive analysis. Data collection was obtained by conducting direct review of documents, photos, videos. The seren tau ceremony is a cultural activity in West Java. In its implementation, the ceremony has a variety of cultural activities in which it has its own value and meaning. These activities can be used as educational media for elementary school students as an effort to build character.